Early Childhood Education Psychoeducation during the COVID-19 - Rikha Surtika Dewi; Maesaroh Lubis; Elfan Fanhas F Khomaeny; Fajar Nugraha; Lusiana Tapiah (AbdimasMu UMTAS, 2022)
The COVID 19 pandemic has made various changes in people's lives, also on Early Childhood Education. The Children hve been affected both directly and indirectly in formal and non-formal education, both education by parents and related institutions. Early Childhood Education and components of the system of education encountered various obstacles related to the implementation of children's activities during social restrictions. Referring to this problem, this Community Partnership Program activity is intended as an effort to anticipate obstacles that occur in Early Childhood Education during the pandemic situation. This Community Partnership Program is implemented through the Psychoeducation Activity Program which focuses on Early Childhood Education. The Psychoeducation Program use an intervention method that can be applied to individuals, families, and groups that focus on educating participants about significant challenges in life, helping participants develop sources of support and social support in facing, and developing coping skills to face these challenges